An analysis of symptom reduction in a sample of adults participating in an intensive outpatient eating disorder treatment program - Scanes, Holly, author; Rickard, Kathryn, advisor; Henry, Kimberly, committee member; Miller, Kimberly, committee member; Dakin, Emily, committee member (Colorado State University. Libraries, 2012)
There is a need for research evaluating the effectiveness of current eating disorder treatment programs (Sullivan, 2002; Wilson, Grilo, & Vitousen, 2007). This study aimed to address this issue through analyzing data obtained from an adult population attending a group-based intensive outpatient treatment program for disordered eating at the La Luna Center for Eating Disorders in Northern Colorado. Data assessing eating disorder-related symptomatology was collected from program participants at the beginning and end of treatment. Program graduates were also provided with a survey asking for feedback about components of the program that were considered helpful to their recovery. Quantitative analyses demonstrated a significant degree of symptom reduction experienced by participants after program completion, and qualitative analyses identified components of the program participants found to be particularly helpful to their recovery. Results of this study provided preliminary support for a theoretically integrated group-based treatment program for eating disorders and highlighted both personal and program factors that may positively impact recovery.
Keywords: anorexia nervosa; bulimia nervosa; eating disorder; eating disorder treatment; intensive outpatient treatment; treatment program